2019
DOI: 10.1016/j.foodchem.2019.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Modified phosphatidylcholine with different alkyl chain length and covalently attached caffeic acid affects the physical and oxidative stability of omega-3 delivery 70% oil-in-water emulsions

Abstract: Modified phosphatidylcholine with different alkyl chain length and covalently attached caffeic acid affects the physical and oxidative stability of omega-3 delivery 70% oil-in-water emulsions. Food Chemistry, 289,[490][491][492][493][494][495][496][497][498][499]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
6
24
0
1
Order By: Relevance
“…Interfacial tension -pendant drop method. The dynamic interfacial tension of the peptides at the oil-water interface was determined using an automated drop tensiometer OCA20 (DataPhysics Instruments GmbH, Filderstadt, Germany) at 25 °C 38 . Peptide solutions (0.2 wt.%) in 10 mM sodium acetate − 10 mM imidazole buffer (pH 7) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Interfacial tension -pendant drop method. The dynamic interfacial tension of the peptides at the oil-water interface was determined using an automated drop tensiometer OCA20 (DataPhysics Instruments GmbH, Filderstadt, Germany) at 25 °C 38 . Peptide solutions (0.2 wt.%) in 10 mM sodium acetate − 10 mM imidazole buffer (pH 7) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Natural antioxidants are preferred as being safer (Kiokias & Varzakas, 2014). The use of hydrolysed proteins (Li et al ., 2019), polysaccharides (Shi et al ., 2020) and modified phosphatidylcholine (Yesiltas et al ., 2019) as natural antioxidants to restrain lipid oxidation in O/W emulsions has been well evaluated. Within the natural antioxidants category, phenolic compounds have emerged as a group of natural antioxidants potentially useful in the food industry, due to their remarkable radical scavenging capability.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugation and resonance effects in caffeic acid occur due to the presence of the CH=CH bridge between the aromatic ring and the carboxyl group. Thus it may act as a chain-breaking antioxidant via donating an H-atom to free radicals or metal chelator to reduce the activity of prooxidant (Conde et al, 2011;Yesiltas et al, 2019) The antioxidative effectiveness of caffeic acid in oilin-water emulsions is mainly attributed to the retardation of initiation and propagation stages of lipid oxidation reactions by scavenging lipid radicals and forming a low-energy phenoxyl radical that does not readily stimulate oxidation of unsaturated fatty acids (Conde et al, 2011;Maqsood & Benjakul, 2010;Sorensen et al, 2008). Gulcin (2006) found that caffeic acid containing a catechol group with an α,β-unsaturated carboxylic acid chain efficiently F I G U R E 4 Chemical structures of different types of phenolic antioxidants quenched the reactive oxygen species, that is, superoxide anion radicals ( • O 2 − ) and singlet oxygen ( 1 O 2 ), and thus showed 75.8% inhibition of lipid peroxidation in linoleic acid oil-in-water emulsions.…”
Section: Caffeic Acidmentioning
confidence: 99%